Multiple Biliary Stones: a Rare Long-term Complication after Whipple Procedure - Kirschbaum-Rubin, Steven (2022)
A hypertensive, diabetic woman underwent a successful Whipple procedure at the age of 84 due to carcinoma of the ampulla of Vater. She presented an extremely rare complication 24 months after the surgery, consisting of acute cholangitis due to multiple biliary lithiases associated with a bilioenteric anastomotic stricture. The diagnosis was confirmed with computed tomography, magnetic resonance cholangiopancreatography, and cholangiography. The patient was successfully treated with multiple percutaneous transhepatic cholangioplasties.